Rozwiąż poniższe równania:


1) 2x + 7 = 6x +8
2) -3x + 4 = -9x + 15
3) -6 - 4x = 15 - 6x
4) 9 - 8x = 19 + 12x
5) 3(x + 9) - 2 = 22
6) 4(5x + 7) + 5 = 41
7) -8(4 - 3x) + 12 = 92
8) 5x + 3 + 4x = 8 + 15x + 4
9) 7x - 4 - 2x = 6x - 12 - 10x
10) 6 - 11x + 19 = 4x - 7 + 3x
no i tak jest dzk


Odpowiedź :

Odpowiedź:

1)

2x + 7 = 6x +8

2x - 6x = 8 - 7

- 4x = 1

x = 1 : (-4)

x= - 0,25

spr.

2x + 7 = 6x +8

L= 2x + 7 = 2* (-0,25) + 7 = - 0,5 + 7 = 6,5

P= 6x + 8 = 6 * (-0,25) + 8 = - 1,5 + 8 = 6,5

6,5 = 6,5

L=P

2)

-3x + 4 = -9x + 15

-3x + 9x = 15 - 4

6x = 11

x= 11 : 6

x= 11/6

x= 1 i 5/6

spr.

-3x + 4 = -9x + 15

L= - 3x + 4= -3* 1 i 5/6 + 4= - 3* 11/6 + 4= -1 *11/2 + 4= - 11/2 + 4= - 5 i 1/2 + 4=

= - 1 i 1/2

P = - 9x + 15 = - 9 * 1 i 5/6 + 15= - 9 * 11/6 + 15= - 3 * 11/2 + 15= - 33/2 + 15=

= - 16 i 1/2 + 15= - 1 i 1/2

- 1 i 1/2 = - 1 i 1/2

L=P

3)

-6 - 4x = 15 - 6x

-4x + 6x = 15 + 6

2x = 21

x= 21 : 2

x= 10,5

spr.

-6 - 4x = 15 - 6x

L= -6 - 4x= -6 -4*10,5 = -6 - 42= - 48

P= 15 - 6x= 15 -6*10,5= 15 - 63 = - 48

-48 = - 48

L=P

4)

9 - 8x = 19 + 12x

-8x - 12x = 19 - 9

- 20x = 10

x= 10 : (-20)

x= - 0,5

spr.

9 - 8x = 19 + 12x

L= 9 - 8x= 9 - 8*(-0,5) = 9 - (-4) = 9 + 4= 13

P= 19 + 12x = 19 + 12*(-5) = 19 + (-6) = 19 - 6 = 13

13=13

L=P

5)

3(x + 9) - 2 = 22

3x + 27 - 2= 22

3x + 25 = 22

3x= 22 - 25

3x = - 3

x= - 3 : 3

x= - 1

spr.

3(x + 9) - 2 = 22

L= 3(x + 9) - 2= 3(-1 + 9) - 2= 3*8 - 2= 24 - 2= 22

P= 22

22=22

L=P

6)

4(5x + 7) + 5 = 41

20x + 28 + 5 = 41

20x + 33 = 41

20x = 41 - 33

20x= 8

x= 8 : 20

x= 0,4

spr.

4(5x + 7) + 5 = 41

P = 4(5x + 7) + 5 = 4(5*0,4 + 7) + 5= 4(2 + 7) + 5= 4*9 + 5 = 36 + 5= 41

P= 41

41=41

L=P

7)

-8(4 - 3x) + 12 = 92

- 32 + 24x + 12 = 92

24x  - 20 = 92

24x = 92 + 20

24x = 112

x= 112 : 24

x = 112/24

x= 4 i 16/24

x= 4 i 2/3

spr.

-8(4 - 3x) + 12 = 92

L= -8(4 - 3x) + 12 = -8(4 - 3* 4 i 2/3) + 12= -8(4 - 3*14/3) + 12=

= - 8 (4 - 1 * 14/1)+ 12 = -8(4 - 14) + 12 = - 8 *(-10) + 12 = 80 + 12 = 92

P = 92

92 = 92

L =P

8)

5x + 3 + 4x = 8 + 15x + 4

9x + 3 = 15x + 12

9x - 15x = 12 - 3

- 6x = 9

x = 9 : (-6)

x = - 1,5

spr.

5x + 3 + 4x = 8 + 15x + 4

L = 5x + 3 + 4x = 9x + 3 = 9*(-1,5) + 3 = - 13,5 + 3 = - 10,5

P = 8 + 15x +4 = 15x + 12 = 15*(-1,5) + 12 = - 22,5 + 12 = - 10,5

- 10,5 = - 10,5

L = P

9)

7x - 4 - 2x = 6x - 12 - 10x

5x - 4 = -4x - 12

5x + 4x = - 12 + 4

9x = - 8

x = - 8 : 9

x = - 8/9

spr.

7x - 4 - 2x = 6x - 12 - 10x

L = 7x - 4 - 2x =5x - 4 = 5*(-8/9) - 4 = - 40/9 - 36/9 = - 76/9 = - 8 i 4/9

P = 6x - 12 - 10x = - 4x - 12 = - 4*(-8/9) - 12 = 32/9 - 108/9 = - 76/9 = - 8 i 4/9

- 8 i 4/9 = - 8 i 4/9

L=P

10)

6 - 11x + 19 = 4x - 7 + 3x

- 11x + 25 =7x - 7

- 11x - 7x = - 7 - 25

- 18x = - 32

x = - 32 : (- 18)

x = 32/18

x = 1 i 14/18

x = 1 i 7/9

spr.

6 - 11x + 19 = 4x - 7 + 3x

L = 6 - 11x + 19 = - 11x + 25 = - 11*1 i 7/9 + 25 = - 11 * 16/9 + 25=  - 176/9 + 25=

= - 19 i 5/9 + 25 = 5 i 4/9

P = 4x - 7 + 3x = 7x - 7 = 7 * 1 i 7/9 - 7 = 7 * 16/9 - 7 = 112/9 - 7 =

= 12 i 4/9 - 7 = 5 i 4/9

5 i 4/9 = 5 i 4/9

L = P

Szczegółowe wyjaśnienie: